Study of plasmonic bandgap by optimization of geometrical parameters of metallic grating devices. (March 2021) - Iqbal, Tahir; Tehseen, Aqsa; Bashir, Almas; Afsheen, Sumera; Tahir, M.B.; Abrar, M.
Abstract: The optimization and comparison of different geometrical parameters of metallic nano-gratings that affect the plasmonic bandgap significantly is being reported in the present research work. The optimization and comparison of geometrical parameters of metallic nano-grating has been important subject to the development of plasmonic devices and systems. This study presents the effect of far field reflection spectra of 1D buried and exposed gratings designed in COMSOL on the plasmonic bandgap using the finite element analysis. In this work, we demonstrated various new trends of PBG energy in gold (Au) nano-gratings by controlling slit width, periodicity and film thickness. The variation of incidence angle of p-polarized light is also studied for the angular dependence, which shows corresponding opening of PBG in the dispersion curves. Abstract : These nano-grating devices are useful in many real-life applications like selective absorbers, photodiodes and light emitting diodes (LEDs) etc.